Storytelling: A Path to Imagination and Creativity in the Primary English Class - Barreto Correa Gloria (Universidad Nacional de Colombia, 2002)
Storytelling has been used as a means to help students of a private school improve their communicative skills. To achieve this goal, we have designed activities that enable students to use English actively and at the same time get in touch with literature. We expect to change students¿ attitudes towards English and to motivate them to develop proficiency in the foreign language through storytelling. In doing so, we are innovating our teaching practices by incorporating a tool that can provide students with both the means and the motivation for using the language and thus develop their communicative skills.